Update on supra-annular sizing of transcatheter aortic valve prostheses in raphe-type bicuspid aortic valve disease according to the LIRA method. (18th May 2022) - Iannopollo, Gianmarco; Romano, Vittorio; Esposito, Antonio; Guazzoni, Giulia; Ancona, Marco; Ferri, Luca; Russo, Filippo; Bellini, Barbara; Buzzatti, Nicola; Curio, Jonathan; Prendergast, Bernard; Montorfano, Matteo
Abstract: Recent evidence has shown that transcatheter heart valve (THV) anchoring in bicuspid aortic valve (BAV) patients occurs at the level of the raphe, known as the LIRA (Level of Implantation at the RAphe) plane. Our previous work in a cohort of 20 patients has shown that the delineation of the perimeter and device sizing at this level is associated with optimal procedural outcome. The goals of this study were to confirm the feasibility of this method, evaluate 30-day outcomes of LIRA sizing in a larger cohort of patients, assess interobserver variation and reproducibility of this sizing methodology, and analyse the interaction of LIRA-sized prostheses with the surrounding anatomy. The LIRA sizing method was applied to consecutive patients presenting to our centre with raphe-type BAV disease between November 2018 and October 2021. Supra-annular self-expanding THVs were sized based on baseline CT scan perimeters at the LIRA plane and the virtual basal ring. In cases where there was discrepancy between the two measurements, the plane with the smallest perimeter was considered the reference for prosthesis sizing. Post-procedural device success, defined according to Valve Academic Research Consortium-2 (VARC-2) criteria, was evaluated in the overall cohort. A total of 50 patients (mean age 80 ± 6 years, 70% male) with raphe-type BAV disease underwent transcatheter aortic valve replacement (TAVR) using different THV prostheses. The LIRA plane method appeared to be highly successful (100% VARC-2 device success) with no procedural mortality, no valve migration, no moderate-severe paravalvular leak, and low transprosthetic gradients (residual mean gradient 8.2 ± 3.4 mmHg). There were no strokes, no in-hospital or 30-day mortality, and an incidence of in-hospital pacemaker implantation of 10%. Furthermore, measurement of the LIRA plane perimeter was highly reproducible between observers ( r  = 0.980; P  < 0.001) and predictive of the post-procedural prosthetic valve perimeter on CT scanning ( r  = 0.981; P  < 0.001). We confirm the feasibility of supra-annular sizing using the LIRA method in a large cohort of patients with high procedural success and good clinical outcomes at 30 days. Application of the LIRA method optimizes THV prosthesis sizing in patients with raphe-type BAV disease.